Socio-cultural factors and nursing ethical dilemma affect stunting in indonesian children - Elvira La Bula; Fitri Arofiati (THE JOURNAL OF Mother and Child Health Concerns, 2025)
Background: Stunting is a body condition that occurs due to chronic malnutrition due to the lack of fulfillment of nutritional needs over a long period of time. In Indonesia, it is estimated that almost less than 20% of children are stunted. Purpose: to outline the socio-cultural factors and ethical dilemmas of nursing that contribute to stunting in children in Indonesia. Method: To achieve this goal, the author conducted a systematic review of quantitative research articles that addressed the topic. Article searches were conducted through Google Scholar and ScienceDirect using keywords such as "social," "cultural," "ethical," "stunting," "child," and "Indonesian." Relevant articles, published within the last five years (2020-2025), and available in Indonesian and English, are then selected based on the inclusion and exclusion criteria that have been set. Search results resulted in ten articles that met the criteria. Results: From the ten articles, eight main themes were found that became socio-cultural factors and ethical dilemmas of nursing related to stunting in children in Indonesia. These themes are based on the results of the journal analysis: nutritional intake of pregnant women, exclusive breastfeeding, complementary breastfeeding (MPASI), community attitudes towards stunting, childcare patterns, environmental cleanliness, as well as economic and educational aspects of parents. Conclusion: Through this systematic review, this study succeeded in revealing how complex socio-cultural factors are interrelated and contribute to the occurrence of stunting in children in Indonesia. These factors include the nutritional adequacy of the mother during pregnancy, the success of exclusive breastfeeding, complementary feeding practices, public views on stunting, the parenting methods applied, the quality of environmental sanitation, as well as the economic conditions and education level of parents.